Effect of environmental education on the knowledge of aquatic ecosystems and reconnection with nature in early childhood. - Maria João Feio (PLoS ONE, 2022)
Blue and green ecosystems are considered a key for the improvement of cities sustainability, providing numerous ecosystem services and habitat for many species. However, urban streams are still neglected and degraded, specially in southern European countries. One important step towards the rehabilitation of these ecosystems is the awareness of their importance by citizens. This study aimed to assess the effect of 1-year of activities (field and laboratory) of an environmental education project on primary school children, in improving their knowledge on urban stream ecosystems and their problems. We analyzed students' questionnaires before and after field and laboratory activities, drawings and group interviews. Initially, most children had incipient contact with rivers and streams, showing fears and lack of knowledge about them. As the project progressed, their perceptions changed, with a clear increase in the proportion of students recognizing the biodiversity associated to rivers (e.g., names of riparian trees, aquatic plants and invertebrates). Also, their fears decreased significantly, while their awareness to the impacts of artificialization and lack of riparian vegetation increased. Our results show that direct contact with nature have a positive role in the way it is understood by children, as well as promoting responsible and sustainable behaviors, being effective from the early primary-school years.